Digital Work Training in Islamic Boarding Schools: A Strategic Model for Enhancing Santri Employability and Reducing Youth Unemployment in Urban Indonesia - Wahyudi Widodo; Saifuddin Chalim; Nuur Halimatus Saadiah Masrukhin; Yandri Susanto; Fadly Usman; Muhammad Husnur Rofiq (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
The purpose of this study is to analyze the extent to which digital training in Islamic boarding schools can improve students’ skills, expand job opportunities, and reduce unemployment in Malang City. This study uses a descriptive qualitative approach with a case study type. Primary data were obtained through in-depth interviews with students, Islamic boarding school administrators, and training instructors, as well as participant observation of digital training activities. Secondary data were obtained from Islamic boarding school documents, reports from the Malang City Manpower Office, and previous research related to unemployment and digital-based education. This study was conducted for four months, from February to May 2025. The research data were analyzed using several analytical methods, namely SWOT and Logic Model. The results show that job digitalization training in Islamic boarding schools can improve students’ technological literacy, particularly in digital marketing, basic graphic design, and online store management. Some students who participated in the training succeeded in developing digital-based micro-businesses or earning income through online freelancing. This study also found that infrastructure factors, instructor competence, and support from the local government, the business world, and alum networks greatly influenced the success of the training. Job digitalization training is one of the strategic and realistic solutions to address student unemployment in Malang City in the digital era.